OptiBra study, a randomized controlled trial on optimal postoperative bra support after breast cancer surgery. (April 2023) - Backman, Malin; Hassan-Nur, Mona; Fridblom, Karolina; Johansson, Hemming; Fredholm, Hanna; Fredriksson, Irma
Abstract: Aim: This randomized controlled trial aimed to compare two different postoperative bras after breast cancer surgery and evaluate their impact on primary outcome pain. Method: The study included 201 patients scheduled for primary surgery (breast conserving surgery with sentinel node biopsy or axillary clearance, mastectomy, or mastectomy with primary implant reconstruction with sentinel node biopsy or axillary clearance). Participants were randomized to either a soft bra or stable bra with compression. The patients were recommended to use the bra 24 h/day for 3 weeks, record daily pain (NRS), analgesic use and hours of bra use. Results: Follow up was completed by 184 patients. No significant differences between the arms were found considering pain score over time, neither day 1–14, nor after 3 weeks. Sixty-eight percent of all patients, regardless of randomization, reported pain during the first 14 days. After 3 weeks 46% still reported pain in the operated breast. Among these, patients randomized to the stable bra with compression reported significantly lower pain score than those randomized to the soft bra. Patients who used the stable bra with compression reported significantly higher levels of comfort, sense of security during activity, less difficulty moving the arm, as well as support and stability for the operated breast compared to those using the soft bra. Conclusion: Using a stable bra with compression is the optimal evidence-based choice after breast cancer surgery to reduce remaining pain 3 weeks after surgery, increasing mobility, comfort, and sense of security. Trial registration number: NCT04059835 at www.clinicaltrials.gov . Highlights: Using a stable bra with compression is the optimal evidence-based choice to reduce pain after breast cancer surgery compared to soft bra. A stable bra with compression increases the patient's mobility, comfort, and sense of security after breast cancer surgery. Benefit of less pain after breast cancer surgery, have high clinical relevance for the patient to improve recovery and quality of life.